Model dan Simulasi Rangkaian RLC Menggunakan Aplikasi Matlab Metode Simulink - Ikhsan Parinduri (Smart Education, 2018)
The simulation approach begins with the development of a real system model. The model should be able to show how the various components in the system interact so that it really describes the behavior of the system. The RLC circuit is either a circuit connected with parallel or in series, but the circuit must consist of a capacitor; inductor; and resistors. RLC naming itself also has its own reasons, namely due to the name of the electrical symbol is usually on the capacitance; inductance and resistance respectively. This circuit will resonate in the same way that is-as the LC circuit. Keywords: model and simulation, RLC series